2017
DOI: 10.1111/jace.15191
|View full text |Cite
|
Sign up to set email alerts
|

Parameters for spray drying ZnO nanopowders as spherical granules

Abstract: Spray drying is a versatile method to perform atomization, drying, and granulation.Spray dryers enable agglomeration of particles into a spherical granule form with a nano-meter size and thus very high specific surface areas (SSA). For this, the synthesized Zn(OH) 2 precipitate should be concurrently atomized and dried under desired spray drying conditions. The drying process has many complex and critical parameters. In order to obtain ZnO nanopowders in a spherical granule form the inlet temperature and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
(185 reference statements)
0
2
0
Order By: Relevance
“…Many current efforts explore the use of particle reactors for STWS due to high surface area relative to monolith structures and for the ability to flow around a system. Spray drying is commonly employed to make high‐performance, fluidizable particles for chemical looping combustion and other applications …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many current efforts explore the use of particle reactors for STWS due to high surface area relative to monolith structures and for the ability to flow around a system. Spray drying is commonly employed to make high‐performance, fluidizable particles for chemical looping combustion and other applications …”
Section: Introductionmentioning
confidence: 99%
“…Many groups have found that the composition and properties of the feed solution/slurry has a significant impact on final particle properties . Feed suspensions comprise micrometer sized particles and thus can be considered a colloidal dispersion .…”
Section: Introductionmentioning
confidence: 99%